(untitled) (African Journal of Biomedical Research, 2019)
The current level of morbidity and mortality among dogs due to canine distemper virus infection raise concerns about the effectiveness of commercially available DHLPPi vaccines. The prevalence of the disease despite vaccination warranted the evaluation of the potency of vaccines that are used for routine vaccination in Nigeria. This study was conducted to investigate antibody responses to the three common brands of DHLPPi vaccines for dogs and to recommend the best immunogenic brand for routine vaccination in dogs in Nigeria. Twenty local breed of dogs, age 8 -14 weeks were purchased from dog breeders in Ibadan, Oyo-State, Nigeria. The dogs were screened for heamoparasites and endoparasites. Those that were positive were treated appropriately and they were acclimatized for three weeks in the University of Ibadan Veterinary Teaching Hospital kernels. They were divided into four groups tagged A, B, C and D. They were fed with rice and meat and formulated rations and served fresh clean water ad-libitum. Groups A, B and C were vaccinated while Group D was not vaccinated and served as the control. Blood samples were collected before vaccination (day 0) and weekly for four weeks and 90 days post-vaccination. The sera of collected blood samples were subjected to ELISA test. Mean values of ELISA antibody titers were calculated and the mean values obtained were compared for significant differences using ANOVA test and student t-test. The antibody titres of the three groups A, B and C were observed to increase within a week of vaccination, and the three vaccinated groups showed variable antibody responses on different days of samplings.characterised with rising and waning of antibodies. Group D was observed to be low titres of antibody throughout the study period. From these findings, all the vaccines were potent, however, comparatively vaccine C was the best, vaccine B was better than A. Vaccine C is therefore strongly recommended for use in dogs for routine vaccination and a booster dose should be administered 4-5 weeks after first dose for optimum humoral immunity against canine distemper virus infection. Seromonitoring is essential in planning vaccination regimen for dogs. Other factors that can affect the effectiveness of vaccine during storage, transportation and administration should be considered for a desirable result